Análise da implementação do programa de Tutoria na Atenção Primária à Saúde em municípios do oeste do Paraná que receberam o Selo Prata - Cavalli, Adriana Andrade dos Santos (2020)
The research has as its object the Tutoring Program in Primary Care (PTAPS) that entered the Paraná scenario in 2014 as a proposal to verify the applicability and incorporation of the quality concepts proposed by the Primary Health Care Qualification Program (APSUS). The PTAPS worked to certify participating teams through quality seals (bronze, silver, gold and diamond), trough the evaluation of processes. This research is characterized as exploratory and descriptive, with a mixed approach, with the general objective: Analyze the implementation process of the Tutoring Program in PHC in teams of the 10th Regional Health of Paraná, awarded with the Silver Seal, from the perspective of tutors and team coordinators. The study sample comprised team tutors (n=5) and coordinators of the health units that received this seal under the 10th Regional Health of Paraná (n=8). Data were obtained through the application of a semi-structured questionnaire to the coordinators and tutors, from January to October 2019. The data comprised information about the profile of the research subjects, the process of implementation and main changes in the work process of the skis, having as parameter the objectives and goals of the program. The results showed that both coordinators and tutors are mostly women (88%); work in the services between five and ten years (62,5%); 100% of the coordinators are nurses, tutors are trained in different health professions. The program’s support, in general, did not go through discussion processes in the teams, generating initial resistance and the view that it would bring work overload. Another factor observed was the low participation of managers, the community different phases of the programmer. Although with variations, both tutors and team coordinators, they valued the experience and recognized that there were changes in the physical structure, in the work process of the teams and in the data recording, which allowed a better understanding of the community’s problems, particularly those with chronic diseases, enabling better planning of local actions. It is concluded that policies and programs such as PTAPS, have an inductive and permanent education character that mobilizes teams, however, changes in state management and the frequent turnover of professionals lead to discontinuities that put the observed advances at risk.